Exosomes derived from HEK293T cells interact in an efficient and non-invasive manner with mammalian sperm in vitro - Coward, K; Vilanova-Perez, T; Jones, C; Balint, S; Dragovic, R; Dustin, M; Yeste, M (Future Medicine, 2020)
Aims: To investigate exosomes as a non-invasive delivery tool for mammalian sperm.